Rancang Bangun Sistem Pengukuran Kematangan Buah Apel Manalagi Menggunakan Sensor Ultrasonik Piezoelectric - Dinanda, Kurniawan Fahmi; Ro`uf, Abdul (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2025)
This study aims to design and test a non-destructive ripeness measurement system for Manalagi apples (Malus Sylvestris) using a piezoelectric-based ultrasonic sensor. Manalagi apples have green skin that does not show any significant changes when ripe, so the visual method is less effective in assessing their ripeness. The designed system utilizes ultrasonic waves to measure the attenuation of waves as they propagate through the fruit. The attenuation results are then correlated with the dissolved sugar content (measured in °Brix) using a refractometer as a comparison. This method offers a faster, more efficient, and less destructive alternative to conventional methods that require fruit extraction. The system prototype consists of a microcontroller, signal amplifier circuit, piezoelectric transducer, and digital oscilloscope to display the waves. The results of the wave measurement test showed that the higher the sugar content in the fruit, the greater the attenuation value produced. Regression analysis of the data obtained provides an equation of y = –40.28 – 0.486x with a coefficient of determination (R²) of 0.6299. This finding provides an important contribution to the development of non-invasive methods for fruit quality analysis, as well as being the basis for further research aimed at improving the accuracy of fruit characteristic predictions through a multivariable approach